Design of cylindrical metashells with piezoelectric materials and digital circuits for multi-modal vibration control - Yin, Danjie; Yi, Kaijun; Liu, Zhiyuan; Zhang, Anfu; Zhu, Rui (Frontiers in Physics, 2022)
Thin-walled cylindrical shells are widely used in industries, such as the main parts of aircrafts, rockets and submarines. Except meeting the load-bearing capacities, such structures must also have good vibration and acoustic performances. However, it is still a challenge to control the multi-modal vibration of cylindrical shells at low frequencies. This paper explores the cutting-edge local resonant piezoelectric metamaterials to control the low-frequency vibration of cylindrical shells. A novel cylindrical meta-shell with piezoelectric materials and digital circuits is proposed, and a multi-resonance transfer function is implemented in each digital circuit. A method to optimizing the parameters in the transfer function for the purpose of vibration reduction is developed. The vibrational characteristics of the meta-shell are numerically analyzed using the finite element method. Numerical results clearly demonstrate that, by delicately designing the parameters in the transfer function, the meta-shell can reduce the peak amplitudes of the first five modes by 30 dB or more. Therefore, the proposed piezoelectric cylindrical meta-shell may open new opportunities in vibration mitigation of transport vehicles and underwater equipment.